2021
DOI: 10.1111/hex.13360
|View full text |Cite
|
Sign up to set email alerts
|

Insights into how Malaysian adults with limited health literacy self‐manage and live with asthma: A Photovoice qualitative study

Abstract: Background: Adjusting to life with a chronic condition is challenging, especially for people with limited health literacy, which is associated with low compliance with self-management activities and poor clinical outcomes.Objective: We explored how people with limited health literacy understand asthma and undertake self-management practices.Design: We adapted the arts-based qualitative methodology Photovoice. Setting and Participants:We sampled ethnically diverse adults with asthma and limited health literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
(137 reference statements)
0
15
0
Order By: Relevance
“…39 Lacking of online health information written in the local languages, for example, Malay language in Malaysia, affects people's access and understanding of health information in LMICs. 40 In our study, participants were able to search for but were not confident in appraising online health information. These findings were similar to other eHealth literacy surveys, particularly among patients living with chronic obstructive pulmonary disease and patients with cardiovascular risks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…39 Lacking of online health information written in the local languages, for example, Malay language in Malaysia, affects people's access and understanding of health information in LMICs. 40 In our study, participants were able to search for but were not confident in appraising online health information. These findings were similar to other eHealth literacy surveys, particularly among patients living with chronic obstructive pulmonary disease and patients with cardiovascular risks.…”
Section: Discussionmentioning
confidence: 98%
“… 39 Lacking of online health information written in the local languages, for example, Malay language in Malaysia, affects people‘s access and understanding of health information in LMICs. 40 …”
Section: Discussionmentioning
confidence: 99%
“…people living with chronic respiratory disease and those supporting them) and services are needed while societal stigma continues. People with asthma have described how support groups can be important in helping reduce feelings of shame, and supporting acceptance of their condition [26], while people with posttuberculosis lung disease have suggested that services like pulmonary rehabilitation should include psychological support to help address these challenges [24 ▪ ]. Adjusting language used to describe conditions may be helpful: participants with asthma in a recent intervention development study felt a new approach using nonmedical language, re-framing asthma as involving a healthy mechanism being triggered too easily (rather than a deficiency or weakness), could reduce stigma and self-blame, potentially increasing motivation to adhere to treatments [33 ▪ ].…”
Section: Stigmamentioning
confidence: 99%
“…Adjusting language used to describe conditions may be helpful: participants with asthma in a recent intervention development study felt a new approach using nonmedical language, re-framing asthma as involving a healthy mechanism being triggered too easily (rather than a deficiency or weakness), could reduce stigma and self-blame, potentially increasing motivation to adhere to treatments [33 ▪ ]. In all cases, interventional approaches to address stigma will likely require multilevel input [26], co-developed with the people the intervention will involve and impact (e.g. people with chronic lung disease, professionals and local communities) to be practically and culturally acceptable [19].…”
Section: Stigmamentioning
confidence: 99%
“…A previous study on delivering supported self-management in the context of Malaysian primary care highlighted that the written action plan endorsed by the Malaysian Thoracic Society 10 was not understood by patients possibly because of limited health literacy combined with the language challenges of living in a multilingual society 23 . We have explored this issue in some detail 24 and found that a written action plan is a particularly an important barrier in Malaysia, hence, the need to explore the role of a pictorial action plan in asthma-supported self-management.…”
Section: Introductionmentioning
confidence: 99%